THE EFFECTS OF THE HIGHER EDUCATION EXCHANGE PROGRAMS ON THE ELITES’ IMAGE OF BRAZIL - Gabriela Gomes Coelho Ferreira; Lucas Damasceno Peirera; Amâncio Jorge de Oliveira; Janina Onuki (Revista Tempo do Mundo, 2022)
This article reflects on the Brazilian educational and scientific diplomacy programs, PEC-G and PEC-PG. The first section stands on documental analyses to fund the claim that the program was designed and functions as a soft power tool. In the suit, the article moves on to quantitative analysis aiming to explore the effects of the programs on the recipients' image of Brazil. Although the country's image has suffered due to the political and economic crises, the recipients of the programs reported a less negative image of the country than their peers who were not part of the program.